Investigation on the electrochemical performances of Li4Mn5O12 for battery applications - Zainol, N.H.; Osman, Z.; Kamarulzaman, N.; Rusdi, R. (Springer Verlag (Germany), 2017)
In this study, well-crystallized Li4Mn5O12 powder was synthesized by a self-propagating combustion method using citric acid as a reducing agent. Various conditions were studied in order to find the optimal conditions for the synthesis of pure Li4Mn5O12. The precursor obtained was then annealed at different temperatures for 24 h in a furnace. X-ray diffraction results showed that Li4Mn5O12 crystallite is stable at relatively low temperature of 400 °C but decompose to spinel LiMn2O4 and monoclinic Li2MnO3 at temperatures higher than 500 °C. The prepared samples were also characterized by FESEM and charge-discharge tests. The result showed that the specific capacity of 70.7 mAh/g was obtained within potential range of 4.2 to 2.5 V at constant current of 1.0 mA. The electrochemical performances of Li4Mn5O12 material was further discussed in this paper.